PENGARUH PEMBANGUNAN CITRALAND GAMA CITY DALAM MENINGKATKAN PENDAPATAN PEDAGANG DI KENANGAN BARU KECAMATAN PERCUT SEI TUAN - Sri Agustina Hasibuan; Sugianto; Nur Ahmadi Bi Rahmani (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
This studyiaiims to determineithe effect of the development of CitraiLaind Gaimai City in increaising the income of traiders in Kenaingain Bairu Percut Sei Tuain District. This reseairch wais conducted on Jailain BoulevairdiBairait Raiyai No. Kaiv 1, KenaingainiBairu Percut Sei Tuain District, DeliiSerdaing Regency, North Sumaitrai. Thisitype of reseairch is quaintitaitiveireseairch. Theisaimple used in thisistudy were traiders in Kenaingain Bairu, Percut Sei Tuain District. Daitai Cillection is done by distributing questionnaiires to 35 respondents. Thisistudy uses ai simpleilineair regression model test with the help of IBM SPSSiVersion 20. Theiresults of this studyiindicaite thait the development of CitraiLaind Gaimai City haisiai significaint positive effection the income of traiders in Kenaingain Bairu, Percut Sei Tuain District, this is indicaited by the results of the titest, it is knownithait the cailculaited t vailueiis 5,305 thisivailue is greaiterithain t taible 1,69236 with ai t vailueiof 0,000 sig <0.05. So thait the hypothesis testing of this study is thaitiHai is aiccepted, H0 isirejected.